البعد السياسي في الفكر الاستشراقي - تقي فضيل, أ.م.د. حيدر (Journal of College of Education, 2021)
This study aims to demonstrate the importance of the dimension and the political objective of Orientalism, where is this goal of the most important goals that represented birth true of Orientalism, The West and although he tried and is trying hard to persuade Arabs and Muslims usefulness of these studies and it is in his interest on the part of, and that there was no remote control or very political on the other, but the fact imposes the contrary, the goal of political at the forefront of goals Orientalist and it shows through the consequences of Orientalism is the most prominent war experienced by the Islamic state on the one hand and the political weakness suffered by this state, Orientalism used religion on the one hand and the history of the on the other hand to show that he intended them to the service of Muslims through research in their books and show the benefits of these books, which made some affected thought Orientalist and even defends him, this does not mean at all the lack of sensed danger Orientalist which led him to caution in the reading of the studies Orientalist, and not drift behind every word, but took side of caution because he is well aware of the political dimension in Orientalist thought, and I also know that the soft-spoken can not be aggravated, but cautious and careful in order to preserve the history, religion and Islamic identity.